PROMOÇÃO DA SAÚDE: janelas de oportunidades para reflexão e ressignificação do cuidado em saúde mental para Agentes Comunitários - Diniz, José Adailton Roland (2014)
The changes in health care and its policies led to the emerging need for changes in working posture and way of caring with views on the scope of comprehensive care, such demand contained in the work processes associated with the difficulties of life professionals, in this case the Community Health Agents ACS generate negative feelings sometimes, making them increasingly vulnerable to psychic disorders resulting from these situations. Based on this reality experienced by the ACS, this intervention aims to facilitate reflection and reframing of care in mental health care for this population. The intervention was carried out with 13 ACS Health Center Dr. Antonio Guanare, one of the units that make up the network service Coroadinho District, in the municipality of São Luís- MA. The slum Coroadinh has 53,900 residents. As large slums, aggregates the various problems arising from these populations with sociodemographic characteristics, highlighting the absence or impairment in basic sanitation, presence of high crime rates, drug use and its consequences, in addition to social stigma. Because the action of ACS to be essentially the territory, their work becomes complex and far from being fully achieved, which generates these potential personal conflicts and daily suffering in developing their activities risks. Workshops with use of group strategies, listen and care were performed. Approaching them from their life stories, checking their feelings and needs arising from situations of life and work and ultimately encourages them to attitudinal changes on the problems of life and work, so we found ourselves your experiences and exposure to stressful situations, feelings of pleasure and pain of their daily lives, reflected on the mental health care and allowed up feelings of well being. Was perceived among agents motivational aspects for attitudinal and behavioral changes aimed at self care, evidenced in the planning activities as well as in the evaluation moments. Furthermore the findings point to the need for creation of continuous spaces of care in order to improve the conditions of mental ACS and consequently their performance at work.